PERTIMBANGAN The Concept Of Fasakh Nikah In Fiqh Shafi'iyyah And Its Application Bireun Shar'iyah Court - Husni, Husni (International Journal of Education, Vocational and Social Science, 2023)
Marriage is oriented towards happiness with the concepts of sakinah, mawaddah and mercy, but in fact there is a lot of disharmony that ends in divorce and fasakh. As happened in Aceh, especially in Bireun, in 2022 cases of fasakh marriage by wives reached 419 cases. This study is focused on answering how the concept of fasakh marriage according to the perspective of Syafi'iyyah fiqh and how it is applied at the Syar'iyah Court of Bireuen. This research is a field research. This research is a qualitative research that is descriptive-analytical with a regulatory approach. The data sources are divided into primary sources, namely all references that are directly related to the problem, and secondary sources, namely all references that are not directly related to the problem but support the perfection of this research. The results of the study concluded that the concept of fasakh nikah according to the perspective of Syafi'iyyah fiqh is (1) fasakh due to disability, can be used to perform marriages such as (crazy, leprosy, supak, impotent, genital mutilation, al-qarn, al-ritq), (2) reasons of subsistence, can be submitted for fasakh marriage because it can cause dharar for the wife, (3) fasakh because the husband is unseen, cannot be used as an excuse to perform a marriage and the wife is required to wait for her husband to hear about the husband died, (4) fasakh because the husband is apostate, the act of apostasy in marriage can cancel the contract. As for the fasakh nikah fiqh decisions at the Syar'iyah Court of Bireuen, some are relevant to the concept of fasakh according to Syafi'iyah and some are different from the concept of syafi'iyah.